2016
DOI: 10.1042/bsr20160028
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox genes gain trimethylation of histone H3 lysine 4 in glioblastoma tissue

Abstract: We revealed that in GBM homeobox genes gain tri-methylation on lysine 4 of histone H3 (H3K4me3), whereas the cell–cell adhesion-related cadherin genes lose H3K4me3, suggesting that the H3K4me3 alteration is related to the formation and migration of GBM cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…As research has progressed, the genomic landscape of cancer has been gradually brought into light, and an increasing number of vital genes shared by various cancers [28,29], ERCC4/XPF for example, have been revealed in recent years. The XPF-rs2276466 polymorphism was widely reported to be associated with susceptibility of a wide range of cancers [30].…”
Section: Discussionmentioning
confidence: 99%
“…As research has progressed, the genomic landscape of cancer has been gradually brought into light, and an increasing number of vital genes shared by various cancers [28,29], ERCC4/XPF for example, have been revealed in recent years. The XPF-rs2276466 polymorphism was widely reported to be associated with susceptibility of a wide range of cancers [30].…”
Section: Discussionmentioning
confidence: 99%
“…186,187 The decrease of H3K4me3 content in the promoter was also detected. 188 Christina et al found that the changes in gene expression of various methyltransferases, acetyltransferases, and deacetylases promoted the pathogenesis of GBM. 189 The nuclear expression levels of lysine methyltransferases SETDB1, KMT5B, Suv-39h1, and EZH2 in GBM are upregulated, compared with normal tissues, and correlated with advanced histological grades.…”
Section: Glioblastoma (Gbm)mentioning
confidence: 99%
“…K27M mutation was found in 30% of children with high‐grade GBM, which was related to adverse clinical outcomes 186,187 . The decrease of H3K4me3 content in the promoter was also detected 188 . Christina et al.…”
Section: Abnormal Expression Of Histone‐modifying Enzymes and Human C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown increased and decreased lysine 4 trimethylation levels of histone H3 (H3K4me3) in GBM compared to normal brain tissue [57,58]. These changes can affect the expression of genes involved in critical cellular processes, including cell cycle regulation, DNA repair, and tumor suppression.…”
Section: Histone Methyltransferases and Mirnasmentioning
confidence: 99%